Allopurinol treatment improves renal function in patients with type 2 diabetes and asymptomatic hyperuricemia: 3‐year randomized parallel‐controlled study. (29th December 2014) - Liu, Peng; Chen, Yingying; Wang, Bin; Zhang, Fengmei; Wang, Debao; Wang, Yangang
Summary Objective To investigate the effects of long‐term effective control of serum uric acid on renal function in patients with type 2 diabetes and asymptomatic hyperuricemia. Methods Application of randomized open parallel‐controlled methods, a total of 176 patients with type 2 diabetes and asymptomatic hyperuricemia were selected, and was randomly divided into two groups for allopurinol or conventional treatments, respectively. Changes in urinary albumin excretion rate (UAER), the levels of serum creatinine and glomerular filtration rate (GFR) and the incidence of new‐onset diabetic nephropathy (DN) and hypertension in patients before and after 3 years of treatment were measured and compared between groups. Results There were no statistically significant difference in the baseline clinical characteristics of study participants between two treatment groups (P > 0·05 for all). After 3 years of treatment, compared to the conventional treatment, the allopurinol treatment was more effective in reducing serum uric acid, UAER, serum creatinine (P < 0·01 for all) and increasing GFR (P < 0·01). The intention‐to‐treat (ITT) analysis indicated that the incidence of new‐onset DN and hypertension in the allopurinol group showed a declining trend compared to that in the conventional treatment group, despite a lack of significant difference (P > 0·05). Conclusion Long‐term effective control of serum uric acid can decrease UAER and serum creatinine, increase GFR and may exert kidney protection effects in patients with type 2 diabetes and asymptomatic hyperuricemia.